Dampak Konflik Orangtua-Anak Terhadap Prestasi Belajar Siswa SMAN 1 Lhoksukon Aceh Utara - Rizal Fuzari; Nurhasanah Nurhasanah; Fajriani Fajriani (Program Studi Bimbingan dan Konseling, FKIP Universitas Syiah Kuala, 2016)
ABSTRACTKey word: parents and children conficts – students’ achievementThe successfulness of teenagers goes through his transition period to gain the optimal development influenced by whether he/she has a good relationship with his/her parents and his/her friends or do not. The aim of this study is to reveal the impact of the conflicts towards the achievement of the students in SMAN 1 Lhoksukon, North aceh. Particularly, the study describes the factors that trigger the conflict between teenagers and parents, how to resolve a conflict between parents and children, the impact of the conflicts towards the students’ achievement, descriptions of the students’ achievement experienced conflict between parent and children. The approach used in this study is descriptive qualitative. The data of this study obtained by conducted direct interview with the theachers and students and documentary analysis of the addressed subject. The result of the study suggests that (1) the conflict triggered by daily activities betwee parents and children, (2) Apology is the way to resolve the the conflict between parents and children they are aware that they are mistaken. (3) The impact of the conflict lowers the students motivation while studying so that it will influence.(4) the achivement of students who experience the conflict lower rather than before the conflict occured. The reseacher suggest that parents and childrent are supposed to have a matual believe so that the conflict among them will be able to settled.